2016
DOI: 10.1542/peds.2015-3679
|View full text |Cite
|
Sign up to set email alerts
|

Improving Trainee Education During Family-Centered Rounds: A Resident’s Perspective

Abstract: Dr Stanski conceptualized the topic, drafted the initial manuscript, and reviewed and revised the manuscript; Dr Patel conceptualized the topic and critically reviewed and revised the manuscript; and both authors approved the fi nal manuscript as submitted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Since the AAP began advocating FCRs in 2003, extensive research has been conducted exploring the reception of FCRs among medical staff and patients. [5][6][7][8][9][10][11] A small number of studies 10,12,13 have looked at caregiver satisfaction with FCRs and concluded that they appreciate FCRs for providing better communication and increasing their understanding of their child's condition. Some of these studies also cited suggestions for improvement, which included the need to use more lay terminology.…”
Section: Introductionmentioning
confidence: 99%
“…Since the AAP began advocating FCRs in 2003, extensive research has been conducted exploring the reception of FCRs among medical staff and patients. [5][6][7][8][9][10][11] A small number of studies 10,12,13 have looked at caregiver satisfaction with FCRs and concluded that they appreciate FCRs for providing better communication and increasing their understanding of their child's condition. Some of these studies also cited suggestions for improvement, which included the need to use more lay terminology.…”
Section: Introductionmentioning
confidence: 99%
“…In an era where resident duty hours are restricted and there may be less time for teaching, incorporating more efficient and effective methods are both useful and necessary. 30 …”
Section: Discussionmentioning
confidence: 99%
“…2,3 However, gaps in our evidence prevail, specifically pertaining to vulnerable patient, family, and learner perspectives. [4][5][6][7][8][9][10] Have we adopted FCR as a standard of care prematurely?…”
mentioning
confidence: 99%
“…Family-centered rounds model communication and demonstrate examination findings, but the bedside may not be an optimal environment for all education. [7][8][9][10] When we promote transparency by discouraging conversations away from patients and families, teaching about what differentiates each patient and the broader context of population-based medical decision-making may be missed. One might argue that this education should be at the bedside, but in my experience, extensive discussions about medicine extraneous to an individual's care can be anxiety provoking for families and may not be in their best interest.…”
mentioning
confidence: 99%
See 1 more Smart Citation